Analysis of factors affecting profitability of sharia commercial banks: evidence from Indonesia - Adhi Widyakto; Sugeng Wahyudi (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2021)
The purpose of this research is to find out the consequences of CAR, LDR, NIM, and FDR on the Profitability of Islamic Commercial Banks in Indonesia in the 2015 - 2019 period. Profitability is proxied by ROA as a measure of the amount of profit generated. The sample used in this study is Islamic commercial bank in Indonesia, which has quarterly reports in the 2015 - 2016 period. The number of samples used is 18 banks which are taken by purposive sampling method. The analytical method of this study uses multiple linear regression with the SPSS 25 program which previously had passed the classical assumption test. The results of this research show that CAR has a good and significant impact on ROA. LDR has a bad and significant impact on ROA. NIM has a good and significant impact on ROA. FDR has a good and significant impact on ROA.